Using and understanding medical statistics - Matthews, David E; Farewell, Vernon T (Karger, 1988)
Since the last edition of this book was published, major developments in computer technology have affected both the practice of medicine and the methods of analyzing medical data. These advances make the focus on this revised edition - understanding many of the statistical methods that are used in modern medical studies - all the more important. Two new chapters have been added by the authors. One provides readers with an introduction to the analysis of longitudinal data. The other augments previous material concerning the design of clinical trials, exploring topics such as the use of surrogate markers, multiple outcomes, equivalence trials and the planning of efficacy-toxicity studies. In addition to providing new information and fine-tuning the rest of the book, the authors have reorganized the final six chapters so that the topics build, naturally, on each other. This latest edition is recommended both as an introduction to medical statistics and as a valuable tool in explaining the more complex statistical methods and techniques used today.
Keywords: biometrie; statistika jako téma; Statistics as Topic; demografie; statistika, zdravotnická statistika; Biometry